HUBUNGAN TINGKAT PARTISIPASI IBU DALAM KEGIATAN POSYANDU DENGAN STATUS GIZI ANAK BALITA (STUDI DI KELURAHAN CANGKIRAN KECAMATAN MIJEN KOTA SEMARANG) - Asdhany, Cahaya; Kartini, Apoina (Journal of Nutrition College, 2012)
ABSTRACTBackground: Children under five years of age are included  in group of nutrition’s susceptible. They are on growth and development cycle which need a huge nutrient. The aim of this study is to understand the relationship between mother’s participation levels in posyandu and nutritional status of children under five years of age.Method: Study of analitical observation with cross sectional was used. Subject was a mother in Cangkiran, having children aged between 12-59 month. Subject was taken with proportional stratified random sampling technique. Mother’s participation in posyandu was taken from health care staff’s data, protein and energy intake were taken from food recall 3x24 hours, and nutritional status of children under five years of age was compared with Z-score of WHO 2005. Data was analyzed using Rank-Spearman and partial correlation used SPSS for Windows 19.0 software.Result: Approximately 56,4% of subjects have active participation’s levels in posyandu. Much of the children under five years of age from those have 80,6% good nutritional status (WAZ), 67,7% normal (WHZ), 61,3% normal (HAZ), and 61,3% normal (BMIAZ). There is a relationship mother’s participation levels in posyandu with nutritional status children under five years of age based on WAZ            (p = 0,030 ;  r = 0,651) but not for WHZ (p = 0,998 ;  r = 0,000), HAZ (p = 0,163 ; r = 0,191), and BMIAZ (p = 0,689 ; r = -0,055). This realtionship is also controlled by sufficient levels of energy             (p = 0,047 ;  r = 0,639) and protein (p = 0,003 ; r = 0,823).Conclusion: Increased participation levels of  mother’s in posyandu enhances nutritional status of children under five years of age (based on WAZ). This case is also influenced by sufficient levels of energy and protein.Keyword: mother’s participation levels, posyandu, nutritional status, children under five years of age